POTENSI INTERAKSI ANTAR OBAT PADA PASIEN RAWAT INAP DIABETES MELITUS TIPE-2 DENGAN KOMORBIDITAS HIPERTENSI - Liniati Geografi; Octaviana Maria Simbolon (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Type 2 diabetes mellitus (insulin-dependent diabetes or adult-onset diabetes) is a condition caused by the ineffective use of insulin in the human body. This disease is also often accompanied by hypertension, where these comorbidities can spur severe cardiovascular complications such as heart attacks, strokes and kidney failure. Hospitalised diabetic patients with comorbid hypertension, have the potential to experience drug-related problems / Drug-Related Problems (DRPs), especially Drug-Drug Interactions (DDIs) due to a combination of therapies during the treatment period. The results obtained from the data tracking of 52 patients showed that 21 patients (40%) had the potential to experience DDIs. The types of potential DDI found in this study had 71 kinds variation with 124 events, 5% were major and 95% were moderate. The prevalence of potential interactions between drugs is quite high and varied. Inpatient monitoring of the risk is essential to avoid potential dangers inflicts on patients.